ISOLATION AND RESEARCH OF MORPHOLOGICAL, PHYSIOLOGICAL AND BIOCHEMICAL PROPERTIES OF PSYCHROPHILIC MICROORGANISMS. (Experimental biology, 2021)
Over the past few years, the interest in microorganisms living in extreme ecosystems has increased. It is obvious, that the microorganisms can be research objects of the deeper aspects in cell and molecular biology. Moreover, research of such microorganisms expand the understanding of the variety of physiological and biochemical mechanisms used by living things. Currently, psychrophilic and psychrotrophic microorganisms are significant in the food industry, chemical industry, and agriculture. Psychrophilic and psychrotrophic microorganisms are recognized as a potential source of cold-active enzymes and bioactive compounds. Psychrophilic enzymes work effectively in various industries at low temperatures. Due to the greater flexibility in the protein structure and higher binding capacity with substrates, in general, psychrophilic enzymes (extremozymes / psychrozymes) have a higher catalytic activity (about 10 times more than mesophilic enzymes) at low temperatures.We have investigated the morphological, physiological and biochemical properties of 14 cultures of microorganisms isolated from the regions of East Antarctica. Additionally, there has been isolated 12 cultures from altitudes of 3000-3500 metres above sea level in Maloalmatinsky gorge.The cultures of the isolated microorganisms were screened for the presence of biotechnologically important enzymes. Furthermore, potential producers of proteases, amylases and lipases were identified. Oxidase and catalase activity was determined.